A Bold Introduction to Human–Animal Studies: Review of Margo DeMello, Animals & Society: An Introduction to Human–Animal Studies - Weitzenfeld, Adam (Humanimalia, 2015)
Margo DeMello. Animals and Society: An Introduction to Human–Animal Studies. New York: Columbia University Press, 2012. 488p. 34.50.